Immunogenicity and malaria transmission reducing potency of Pfs48/45 and Pfs25 encoded by DNA vaccines administered by intramuscular electroporation. Issue 2 (5th January 2017) - Datta, Dibyadyuti; Bansal, Geetha P.; Gerloff, Dietlind L.; Ellefsen, Barry; Hannaman, Drew; Kumar, Nirbhay
Abstract: Pfs48/45 and Pfs25 are leading candidates for the development of Plasmodium falciparum transmission blocking vaccines (TBV). Expression of Pfs48/45 in the erythrocytic sexual stages and presentation to the immune system during infection in the human host also makes it ideal for natural boosting. However, it has been challenging to produce a fully folded, functionally active Pfs48/45, using various protein expression platforms. In this study, we demonstrate that full-length Pfs48/45 encoded by DNA plasmids is able to induce significant transmission reducing immune responses. DNA plasmids encoding Pfs48/45 based on native (WT), codon optimized (SYN), or codon optimized and mutated (MUT1 and MUT2), to prevent any asparagine (N)-linked glycosylation were compared with or without intramuscular electroporation (EP). EP significantly enhanced antibody titers and transmission blocking activity elicited by immunization with SYN Pfs48/45 DNA vaccine. Mosquito membrane feeding assays also revealed improved functional immunogenicity of SYN Pfs48/45 (N-glycosylation sites intact) as compared to MUT1 or MUT2 Pfs48/45 DNA plasmids (all N-glycosylation sites mutated). Boosting with recombinant Pfs48/45 protein after immunization with each of the different DNA vaccines resulted in significant boosting of antibody response and improved transmission reducing capabilities of all four DNA vaccines. Finally, immunization with a combination of DNA plasmids (SYN Pfs48/45 and SYN Pfs25 ) also provides support for the possibility of combining antigens targeting different life cycle stages in the parasite during transmission through mosquitoes.